Influence of the Diagnostic and Interactive Use of the Budget on Managerial Performance Mediated by Organizational Commitment - Itzhak David Simão Kaveski; Ilse Maria Beuren; Tayse Gomes; Carlos Eduardo Facin Lavarda (BBR: Brazilian Business Review)
The objective of this study is to evaluate the influence of the diagnostic and interactive use of the budget on managerial performance, as mediated by organizational commitment. A survey was carried out using Brazilian textile industry companies as a population, and the sample consists of 133 respondents to the questionnaire. Structural equation modeling was used to test the hypotheses. The results showed that the diagnostic and/or interactive use of the budget influences organizational commitment, as well as influencing managerial performance. The organizational commitment variable had a total mediating effect on the relationship between the use of budgetary control system and managerial performance, indicating that forms of budget use affect managerial performance only when managers are committed to the organization. Based on the results, we concluded that forms of budget use had influence on organizational commitment and on the managerial performance in the surveyed companies. These results advance the literature as they reveal that the diagnostic use and interactive use of the budget are antecedent variables of organizational commitment, leading to behaviors at work that can contribute to increasing managerial performance.